Use of the hurst exponent for analysis of electrocortical epileptiform activity induced in rats by administration of camphor essential oil or 1,8-cineole - Ćulić, M.; Stojadinović, G.; Martać, L.; Soković, M. (Нейрофизиология, 2010)
In this study, we investigated the presence of long-range correlation effects in the electrocortical activity of rats using the Hurst exponent (H) calculated by dispersion analysis (DA) and an aggregated variance method (AGV). A slow decline of the autocorrelation function during time expansion and the existence of a correlation between distant time points of electrocorticograms (ECoGs) were shown to be typical of various pathophysiological states. In these cases, the H values were within a 0.5 < H < 1 range. A particularly slow decay of the autocorrelation function is typical of a long-range dependence (LRD). We found that ECoGs after i.p. administrations of camphor essential oil or its main constituent, 1,8-cineole, included attacks of uncontrolled electrical discharges and showed the presence of longrange correlation effects. Such findings are in agreement with recent data obtained by other authors and suggest that initiation of seizures can be predicted by certain ECoG indices. We estimated the critical period where the H values for ECoGs containing uncontrolled electrical discharges continuously increased within a few minutes before the attack. We believe that the AGV demonstrates certain advantages over DA in calculations of the H. Ми виявляли присутність ділянок тривалої кореляції в електрокортикограмах (ЕКоГ) щурів, використовуючи побудову експоненти Харста (Н). Останню розраховували на основі дисперсійного аналізу (DA) або методу згрупованих варіанс (AGV). В ЕКоГ, зареєстрованих у різних фізіологічних станах, спостерігалися повільне затухання аутокореляційної функції при розтягненні часової шкали та кореляція між віддаленими часовими точками. У цих випадках значення Н знаходилося в діапазоні 0.5<H<1.0. Особливо повільне затухання аутокореляційної функції свідчить про наявність довгодіапазонної залежності (LRD). Ми встановили, що в ЕКоГ, зареєстрованих після внутрішньоочеревинних ін’єкцій камфорної олії або її основного активного компонента 1,8-цинеолу, були наявні спалахи неконтрольованих розрядів (епілептиформні епізоди) та прояви тривалої кореляції. Ці спостереження узгоджуються з результатами, про котрі повідомляли інші автори, та вказують на можливість передбачати можливий розвиток судомної активності. Як виявилося, критичний період, у межах котрого величина Н для ЕКоГ з наявністю епілептиформних епізодів і котрий передує розвитку судомної активності, складає декілька хвилин. Ми вважаємо, що метод AGV при розрахунку Н має преференції порівняно з DА.